MENINGKATKAN KESADARAN HYGIENE DAN SANITASI MELALUI PROGRAM SOSIALISASI UNTUK PEDAGANG KAKI LIMA DI KELURAHAN SUNYARAGI - Ety Setiawati; Abdul Khalim; Yuke Hernawati; Annisaa Eka Warliati; Dian Fitriana (LPPM Universitas Bina Bangsa, 2024)
Hygiene and sanitation are crucial aspects in maintaining individual and community health, especially in densely populated environments and urban areas. However, a lack of knowledge about correct hygiene practices and limited access to adequate sanitation facilities are the main obstacles in creating a healthy environment. Street vendors (PKL), as a community group that is vulnerable to hygiene problems, are the focus of attention in efforts to improve the quality of life and overall public health. A Participatory Action Research (PAR) approach was applied, actively involving street vendors in every stage of the program. Outreach and education materials include personal hygiene, safe food handling, and proper use of sanitation facilities. This service was carried out by lecturers at the Prima International Tourism Polytechnic for street vendors in the Sunyaragi sub-district. Through this community service activity, it is hoped that there will be an increase in the knowledge, attitudes and behavior of street vendors regarding hygiene and sanitation. The positive impact of this program is not only limited to improving product quality and consumer confidence, but also contributes to reducing the risk of infectious diseases. This service also highlights the importance of cross-sector collaboration in overcoming urban cleanliness problems. It is hoped that similar programs in the future will be able to integrate hygiene practices into people's lives, creating a healthier and more productive environment